Aircraft structural health monitoring using PZT transducers and ultrasonic waves - Nur Hafiszah Binte Abdul Manap. (2011)
Non destructive structural health monitoring has been a constant focus due to its effectiveness in the aircraft industry in damage detection. Early detection of any damages or failures can prolong the service life of aircrafts and serve as an advantage. Using PZT transducers (Piezoelectric transducer), in depth understanding and characteristics of the damage detected can be studied. The main focus of this report is to use the PZT transducer to generate ultrasonic wave and capture the receive signal or response from the structural component. Numerical studies will be developed by Finite Element Analysis technique and validated with respect to the experimental results and theoretical predictions to show the degree where simulations can be used to support further studies. From the wave response received, wave modes and characteristics with respect to the structural damage will be investigated. Double excitations of pure modes are also addressed.